Challenges to develop novel anti‐inflammatory and analgesic drugs. (31st August 2016) - Botz, Bálint; Bölcskei, Kata; Helyes, Zsuzsanna
Abstract : Chronic inflammatory diseases and persistent pain of different origin represent common medical, social, and economic burden, and their pharmacotherapy is still an unresolved issue. Therefore, there is a great and urgent need to develop anti‐inflammatory and analgesic agents with novel mechanisms of action, but it is a very challenging task. The main problem is the relatively large translational gap between the preclinical experimental data and the clinical results due to characteristics of the models, difficulties with the investigational techniques particularly for pain, as well as species differences in the mechanisms. We summarize here the current state‐of‐the‐art medication and related ongoing strategies, and the novel targets with lead molecules under clinical development. The first members of the gold‐standard categories, such as nonsteroidal anti‐inflammatory drugs, glucocorticoids, and opioids, were introduced decades ago, and since then very few drugs with novel mechanisms of action have been successfully taken to the clinics despite considerable development efforts. Several biologics targeting different key molecules have provided breakthrough in some autoimmune/inflammatory diseases, but they are expensive, only parenterally available, their long‐term side effects often limit their administration, and they do not effectively reduce pain. Some kinase inhibitors and phosphodiesterase‐4 blockers have recently been introduced as new directions. There are in fact some promising novel approaches at different clinical stages of drug development focusing on transient receptor potential vanilloid 1/ankyrin 1 channel antagonism, inhibition of voltage‐gated sodium/calcium channels, several enzymes (kinases, semicarbazide‐sensitive amine oxidases, and matrix metalloproteinases), cytokines/chemokines, transcription factors, nerve growth factor, and modulation of several G protein‐coupled receptors (cannabinoids, purinoceptors, and neuropeptides). WIREs Nanomed Nanobiotechnol 2017, 9:e1427. doi: 10.1002/wnan.1427 This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Neurological Disease Abstract : Summary of the main target categories for the development of novel anti‐inflammatory and analgesic drugs.